A mid-term appraisal of the achievements under the five year plan: July, 1964-June 1969 (Dar es Salaam, Ministry of Economic Affairs and Development Planning, 1967)
This mid-term review was made with a view to acquainting the Honourable members and the public at large, the achievements made since the inception of the Five Year Plan up to end of December 1966. The presentation of the report was mainly of a macro nature
Cover title.
osc 07/03/2019
Loans
Keywords: Tanzania; Tanzania